Role of Six1 in Controlling DNA Accessibility and Epigenetic Landscape Dynamics in Myoblasts - Balakrishnan, Ramya (Université d'Ottawa / University of Ottawa, 2022)
Owing to the presence of muscle stem cells (MuSC), adult skeletal muscle is capable of regenerating after injury. Quiescent muscle stem cells become activated and proliferate into myoblasts which undergo myogenic differentiation to repair damaged tissue. The transcription factor (TF) Six1 is a known regulator of muscle stem cells which potentially plays a role in the early stages of MuSC activation. When bound to the appropriate cofactor, Six family transcription factors are capable of activating or repressing transcription. Previous work suggests that Six1 establishes the accessibility landscape required for the myogenic regulatory factor (MRF) MyoD to bind to DNA. It was hypothesized that Six1 recruits p300 to acetylate Histone H3 lysine 122 which then renders DNA more accessible and facilitates gene transcription. The objective of this research was to investigate the role of Six1 in regulating the epigenetic and accessibility state of DNA in myoblasts. It was found that Six1 and the histone acetyltransferase p300 coincide at many gene enhancers. In addition, Six1 knock-down is associated with reduced DNA accessibility at a large number of loci in C2C12 myoblasts and with gene downregulation. In this research, we determined that recruitment of p300 by Six1 alters chromatin accessibility and gene expression in proliferating myoblasts, providing evidence of Six1 pioneer factor activity.
Keywords: myogenesis; muscle; stem cell; epigenetics; accessibility